Nurses’ Perceptions of the Quality of Perinatal Care Provided to Lesbian Women - Tzur-Peled, Sharona; Kushnir, Talma; Sarid, Orly (Frontiers in Psychology, 2022)
Aim Based on the Theory of Reasoned Action (TRA), we examined whether attitudes of nurses from different ethnic groups, subjective norms, behavioral intentions, assessments of relationships and communication were associated with their perceptions of the quality of perinatal care provided to lesbian women. Background Nurses administer healthcare, provide pertinent information and consultation to lesbians from pregnancy planning through birth. Introduction During the past few decades, worldwide, there has been a rise in lesbian-parenting. Despite the changes in Israeli society’s public and legal reality, intolerance and discrimination to the homosexual population is still prevalent in Israel’s healthcare system. Methods A cross-sectional study conducted between 12/2015-4/2016. Of the 270 nurses approached, 184 completed a self-report anonymous questionnaire (a response rate of 74%). Findings This is an important and timely study reflecting nurses’ perceptions of the quality of perinatal care provided to lesbians. The study findings reflect that attitudes, subjective norms, behavioral intentions, assessments of relationships and communication of nurses from different ethnic groups are associated with their perceptions of the quality of perinatal care provided to the lesbians. The hierarchical regression analysis demonstrated that attitudes, subjective norms, behavioral intentions, assessments of relationships and communication of nurses contributed 56% to the variance of nurses’ perception of their own quality of perinatal care. Discussion TRA conceptualization predicted the quality of care of nurses from different ethnic groups treating lesbians in a perinatal setting. Conclusion TRA provides a useful framework for understanding and predicting the motivational effect of health care personnel with the lesbian population, being at risk for stigmatization and receiving less quality perinatal care. Implications for nursing and heath policy Our findings revealed the importance of formulating a recognized policy in the field of LGBT medicine at the national level. Further training of nurses as to the lesbians’ unique health needs, might improve the nurses’ relationships and communication as well as the quality of perinatal nursing care.